N-[2-(4-Acetyl-1-Piperazinyl)Phenyl]-2-(3-Methylphenoxy)Acetamide (NAPMA) Inhibits Osteoclast Differentiation and Protects against Ovariectomy-Induced Osteoporosis - Lee, Jinkyung (Molecules, 2020)
Osteoclasts are large, multinucleated cells responsible for bone resorption and are induced in response to the regulatory activity of receptor activator of nuclear factor-kappa B ligand (RANKL). Excessive osteoclast activity causes pathological bone loss and destruction. Many studies have investigated molecules that specifically inhibit osteoclast activity by blocking RANKL signaling or bone resorption. In recent years, we screened compounds from commercial libraries to identify molecules capable of inhibiting RANKL-induced osteoclast differentiation. Consequently, we reported some compounds that are effective at attenuating osteoclast activity. In this study, we found that N-[2-(4-acetyl-1-piperazinyl)phenyl]-2-(3-methylphenoxy)acetamide (NAPMA) significantly inhibited the formation of multinucleated tartrate-resistant acid phosphatase (TRAP)-positive cells from bone marrow-derived macrophages in a dose-dependent manner, without cytotoxic effects. NAPMA downregulated the expression of osteoclast-specific markers, such as c-Fos, NFATc1, DC-STAMP, cathepsin K, and MMP-9, at the transcript and protein levels. Accordingly, bone resorption and actin ring formation were decreased in response to NAPMA treatment. Furthermore, we demonstrated the protective effect of NAPMA against ovariectomy-induced bone loss using micro-CT and histological analysis. Collectively, the results showed that NAPMA inhibited osteoclast differentiation and attenuated bone resorption. It is thus a potential drug candidate for the treatment of osteoporosis and other bone diseases associated with excessive bone resorption.